Role and contribution of Asian women in decision making process at Shari`ah Councils in the UK - Mohamad Cusairi, Rafidah (2014)
In the UK religious divorce often takes place informally, especially in the resolution of Muslim family disputes. Initially, the unavailability of the civil courts to hear cases relating to Muslim family law and other related problems had strongly persuaded community leaders and religious scholars to establish Shari`ah Councils.This paper seeks to explore the role played by women in decision making process at the Shariah councils in the resolution of matrimonial disputes in particular divorce among the Muslims community in the UK. Process and procedure of issuing an Islamic divorce will be examined.To achieve this, library and empirical methods were adopted.Three main Shari`ah Councils in the UK were visited. Mediation and arbitration sessions as well as Shari`ah Councils’ monthly meetings were observed in order to examine role, participation and contribution of women in the processes. The study leads to several findings.First, the majority of clients are women.Second, most Shari`ah councils do not have female counsellor, mediator or scholar.This associates with the third finding of not recognizing women’s intellectual and emotional capability to take the role. This paper concludes and suggests the potentially significant role of females as mediators-arbitrators as well as counsellors in negotiating matrimonial disputes and that their role should be recognized.